A Research Article on Birth Rituals of Sindh in The Teaching of Islam: سندھ میں رائج رسومات ِ ولادت کا اسلامی تعلیمات کی روشنی میں تحقیقاتی مطالعہ - Shaikh, Muhammad Ali; Rajpar, Dr. Muhammad Aslam (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Ever since Allah, the Exalted, bestowed upon man the blessings and sent him down to earth, happiness and sorrow have been his destiny. Man has to live in this soil for a certain period of time. Life is dependent on various requirements. Due to change in circumstances, change in lifestyle is also a part of nature. It is a great blessing for a person to fulfil all the requirements of his borrowing, and this action also implies that obedience to one’s Lord is real freedom. Instead of worshiping and meditation, the trend towards rituals and customs has reached a very sensitive and dangerous level. Considering onc’e rituals that it is not uncommon to wake up at night. Now there is a dire need to change the course of events and the mood of your thinking. It is important that our religion has perfect guidance for all aspects of life and hereafter. As Muslims, we must remember that we have such restrictions and we have boundaries set by the Allah Almighty, the observance of which is the requirement of servitude. This is not the case with a person who, after reciting the Qur’an, should follow Allah and His Messenger forever. If this is our faith that Islam is the comprehensive and ultimate religion then why we are following such rituals which are totally against the Quran and Sunnah.